Motivation for Adults Learning English in the Work Environment - Narfais, Alma Dita Mia; Lestari , Gunarti Dwi; Widodo, Widodo; Yulianingsih, Wiwin (Lembaran Ilmu Kependidikan, 2024)
The strong desire of adults to learn a language with various heavy considerations is a new resolution in their life in order to improve and hone their abilities to be able to participate in various opportunities. The aim of this research is to find out and identify the motivation for learning English among adults in the work environment. This type of research is qualitative research. The method applied is a qualitative method with a case study approach. The data collection techniques used were participant observation and in-depth interviews with course participants who had established jobs and were over 40 years old. The data analysis technique uses qualitative descriptive analysis. The data analysis model applied is Miles and Huberman, namely data reduction, data presentation and drawing conclusions. The results obtained in this research are that adults' motivation to learn English is most influenced by external aspects, namely pressure and demands from the work environment. Meanwhile, the internal aspect is influenced by individual feelings such as lack of self-confidence (inferior), shyness, and tending to be afraid to express oneself in English.